A phase-field modelling for 3D fracture in elasto-plastic solids based on the cell-based smoothed finite element method. (September 2021) - Guan, Weiyuan; Bhowmick, Sauradeep; Gao, Guangjun; Liu, Gui-Rong
Highlights: The proposed CS-FEM phase-field is an efficient fracture modelling in elasto-plastic solids. The computational cost is slightly lower than the finite element counterpart. Complex crack paths are simulated without any ad hoc criterion. Resultant crack patterns are in excellent agreement with experimental observations. Abstract: Three-dimensional (3D) phase-field models based on the cell-based smooth finite element method (CS-FEM) are established in this paper. The present model consists of three key ingredients: 1) a phase-field model of fracture in elasto-plastic solids, 2) a staggered scheme for nonlinear interactions between the phase-field equations and those for the elasto-plastic solid mechanics, and 3) its underline solution platform of the cell-based smoothed finite element method, CS-FEM. The phase-field model allows effective capturing of the evolution process of complex fracture morphology in elasto-plastic solids. The use of the staggered algorithm gives a practical means to couple the phase field and displacement field in fracturing elasto-plastic solids. The CS-FEM offers important softer model behavior in solving the governing equations. For wide applicability of our Phase-field CS-FEM approach, it is implemented in the commercial software ABAQUS via User Defined Element (UEL) subroutine. Numerical examples of both 2D and 3D benchmark problems with complex crack topologies are presented to verify the accuracy of the solutions. Good agreements are obtained with the experimental observations and existing numerical results in the literature. The phase-field CS-FEM approach offers an effective alternative means to model 3D fracturing in elasto-plastic solids.